Slow Education as a Form of Resistance to the Acceleration of Modern Learning: A Humanistic Approach to Education - Ni wayan Karmini; Made Ayu Anggreni (PT. AVID MEDIA INDONESIA, 2026)
The acceleration of modern education, driven by neoliberal demands, standardized testing, and digital technologies, has fundamentally altered the learning landscape, marginalizing students' well-being, depth of understanding, and intrinsic motivation. This article examines Slow Education as a form of philosophical and pedagogical resistance to these trends, grounded in the humanistic tradition of education. Drawing on a systematic literature review, this study analyzes the theoretical foundations of Slow Education—including its intellectual roots in the Slow Movement and alignment with humanistic psychology—and evaluates its implications for contemporary classroom practice. The findings indicate that Slow Education prioritizes meaningful engagement, emotional safety, autonomy, and the cultivation of critical thinking over efficiency-driven metrics. When integrated with humanistic principles derived from Maslow's hierarchy of needs and Rogers' student-centered learning, Slow Education offers a coherent alternative pedagogy that restores dignity and depth to learning. The study further explores specific strategies contemplative practices, dialogic learning, project-based inquiry, and reduced curriculum coverage that operationalize slow principles in practice. This article contributes to the growing scholarly conversation on pedagogical sustainability, student mental health, and the ethics of care in education, concluding that Slow Education is not merely a nostalgic retreat but a forward-looking humanistic framework urgently needed in an age of educational acceleration.